Adaptive and innate immune responses in multiple sclerosis with anti-CD20 therapy: Gene expression and protein profiles - Fong, Chloe C.; Spencer, Julian; Howlett-Prieto, Quentin; Feng, Xuan; Reder, Anthony T. (Frontiers in Neurology, 2023)
Background Anti-CD20 is a highly effective therapy for multiple sclerosis (MS), a disease with multiple abnormalities in function of B and T cells and innate immune cells. Anti-CD20 therapy depletes B cells, which alters antibody production and has diverse effects on B cell immunity. These changes potentially affect immunity beyond B cells in MS. Objective Determine if anti-CD20 therapy effects non-B cell, as well as B cell, gene expression, and serum protein levels. Methods Samples were collected from 10 healthy controls and from clinically stable relapsing–remitting MS – 10 untreated, 9 interferon-β-treated, and 15 ocrelizumab-treated patients were studied before, and 2 weeks and 6 months after, the first anti-CD20 infusion. Peripheral blood mononuclear cells (PBMC) were analyzed with sensitive, 135,000-transcript RNA expression microarrays, using stringent criteria. Gene expression was compared to 43 MS-relevant serum immune and neurotrophic proteins, using multiplex protein assays. Results Anti-CD20 therapy reduced expression of 413 total genes and 185 B-cell-regulated genes at 2 weeks vs. pre-therapy. Expression of 19 (15%) of these B cell genes returned toward baseline by 6 months, including genes for the B cell activation protein, CD79A, and for immunoglobulin A, D, and G heavy chains. Expression pathways for Th17 and CD4 regulatory T-cell (Treg) development, differentiation, and proliferation also quieted. In contrast, expression increased in Th1 and myeloid cell antiviral, pro-inflammatory, and toll-like receptor (TLR) gene pathways. Conclusion These findings have clinical implications. B cell gene expression diminishes 2 weeks after anti-CD20 antibody infusion, but begins to rebound by 6 months. This suggests that the optimum time for vaccination is soon before reinfusion of anti-CD20 therapy. In addition, at 6 months, there is enhanced Th1 cell gene expression and induction of innate immune response genes and TLR expression, which can enhance anti-viral and anti-tumor immunity. This may compensate for diminished B cell gene expression after therapy. These data suggest that anti-CD20 therapy has dynamic effect on B cells and causes a compensatory rise in Th1 and myeloid immunity.